Societal Responses to CO2 Storage in the UK: Media, Stakeholder and Public Perspectives. (July 2017) - Gough, Clair; Cunningham, Rebecca; Mander, Sarah
Abstract: This paper summarises results from empirical research with the broad aim of exploring societal responses to CO2 storage, framed around the concept of social license to operate (SLO). The essential characteristic of SLO is based on a partnership between communities, operators and government and is thus dependent on a variety of factors that contribute to building trust between the stakeholders. Drawing on data from media analysis, stakeholder interviews and focus groups deployed in two locations in the UK, we explore social factors that could influence an emerging SLO for CO2 storage in the UK, drawing lessons from an analogous technology.